Babatha, En-Gedi And The Bar Kokhba Revolt: A New Approach Using Evidence From The Cave Of Letters - Esler, Philip Francis (Biblical theology bulletin, 2026)
This article presents a new approach to when and where the Bar Kokhba Revolt began and to its aftermath by adopting a microhistorical approach to evidence, both papyri and objects, left by Judean fugitives from the Romans, especially Babatha, daughter of Shim?on, in the Cave of Letters in Na?al ?ever. The central argument is based on P. Yadin 27 of 19th August 132 CE to the effect that it is not a receipt but a draft receipt, meaning that Babatha never received the three months' maintenance for her son that is specified in it. That she sought the third month's payment in advance and other factors suggest that the Revolt had broken out in the week before and that she was in a hurry to join it. An array of factors suggests that Bar Kokhba began his revolt with the capture of En-Gedi, which was Babatha's destination when she left her hometown of Maoza, in Arabia on the south eastern corner of the southern basin of the Dead Sea. At the end of the Revolt she was in the cave in Naḥal Ḥever but three men long believed to be there (Yehonathan, son of Bayʿan, Mesabalah, son of Shimʿon, and Eliezer, son of Shemuel) were not.